EVALUASI PELAKSANAAN DISIPLIN KERJA KARYAWAN BAGIAN LAPANGAN PADA PT. BANGAUMAS PERKASA SIAK SRI INDRAPURA - Rizal Nainggolan; Hendry Andry (UIR Press, 2015)
Human resource is one company that has a value of initiative and have a role as well in theuse of other resources that exist within the company. The concern is how the company'senterprise utilizing human resources in order to work effectively and efficiently inachieving corporate goals. Discipline as a dynamic condition in which individuals arefaced with opportunities, constraints and desires and the results obtained are veryimportant but it can not be ascertained. And one of the problems the company is applyingthe rules to improve the discipline of employees that affect the employee's job performance.According to Sutrisno Discipline is respect for the rules and regulations of the company,which is inside of employees, which causes it to be able to adjust to the provisions of thecompany voluntarily. The formulation of this problem is how the discipline of employeework in the field of PT. Bangaumas Perkasa Siak Sri Indrapura. The purpose of this studywas to determine and explain the discipline of employees at PT. Bangaumas Perkasa SiakSri Indrapura and knowing the obstacles in enforcing discipline in the company working onthe PT. Bangaumas Perkasa Siak Sri Indrapura. This type of research is quantitative type,the research emphasizes on the analysis of numerical data (numbers) are processed withstatistical methods, so as to obtain the significance of the relationship between variables.Methods of data collection was done by a list of questions (quisioner), interviews,observation, and documentation. The operational variables of this research is the disciplineof working hours, discipline dressed and behaved, disciplined task and cooperation withother units, and disciplined about what not to do at work. The results of this research to thediscipline of working hours is good enough, while discipline well dressed and well behavedthe result is not good, disciplined task and cooperation with other units is good enough,and discipline about what not to do when working the results is good enough. Theconclusion of the study showed that the implementation of employees work discipline in thePT. Bangaumas Perkasa is good enough.